Territorial Marketing And Territorial Competitiveness In Algeria - Kheloui, Nassima; Daoudi, Mohammed (جامعة الوادي University of Eloued, 2025)
Territorial marketing plays a key role in the competitiveness of territories by influencing their attractiveness and economic development. Its impacts: economic attractiveness, tourism development, image and reputation, innovation and collaboration, social cohesion, sustainability. Territorial marketing is an essential lever for strengthening the competitiveness of a territory by improving its attractiveness, its image and its ability to innovate, while responding to economic, social and environmental challenges. The objective of this study is to identify the principles of optimising the attractiveness and competitiveness of a territory by putting its specific assets (economic, cultural, natural, etc.) and meeting the expectations of the various target audiences while strengthening the image and reputation of the territory.
مقال
Keywords: Marketing Territorial; Differentiation strategy attractiveness; Territorial innovation; Territorial tourism; Networks of local actors.